Production and distribution of virusfree yam (Dioscorea rotundata Poir.) - Ng, S.Y.C. (International Society for Horticultural Science, 1994)
The international distribution of vegetative plant parts is restricted by the risks of introducing diseases and pests to non-infected areas. Methods used at IITA to produce and distribute virus-free yams to requesting national programs and collaborators are described. The selected yam clones are cleaned from virus disease infection through thermotherapy and meristem culture. The regenerated plants are virus indexed. The negatively indexed plants are then multiplied in vitro for international distribution. Plantlets of about 4–6 cm height grown in sterile culture media are packed for distribution by hand carriage. Node cuttings of the in vitro plantlets are also sub-cultured in a medium containing sucrose (5%) for micro-tuber production. Micro-tubers are harvested from 4–5 months old cultures and packed in sterile petri plates with sterile moist cotton wool for dispatch to national programs. Some virus-free yam plantlets are also transplanted to sterile soil in a screenhouse where they grow to maturity. Harvested tubers are used for distribution. The advantages and disadvantages of each method are discussed.